Sex-specific responses in sleep metrics throughout heat acclimation in highly trained endurance runners - Waller, S.; Keefe, M. S.; Mccollum, T. B.; Dunn, R. A.; Sekiguchi, Y. (International Journal of Exercise Science Conference Proceedings, 2026)
Training in a hot environment (heat acclimation) elicits beneficial physiological and thermoregulatory adaptations that enhance subsequent exercise in the heat; however, additional strain from exertional heat stress may negatively influence sleep duration and quality. Although sex differences in sleep have been observed relative to exercise, it remains unclear if training in the heat exacerbates sex-specific responses.